HER-2/neu expression in germ cell tumours. Issue 9 (1st September 2002) - Soule, S; Baldridge, L; Kirkpatrick, K; Cheng, L; Gilbert, J L; Smith, L R; Thurston, V C; Vance, G H; Einhorn, L; Miller, K
Abstract : Aims: To determine the rate of HER-2/neu positivity of germ cell tumours by immunohistochemistry (IHC) and by fluorescence in situ hybridisation (FISH). Patients/Methods: Ninety six archival, paraffin wax embedded pathology specimens were chosen from four groups of germ cell tumours. IHC for HER-2/neu was performed with the HercepTest kit; FISH analysis was performed with the INFORM assay and confirmed with a centromere 17 probe. Results: Twenty two of 96 specimens overexpressed the HER-2/neu protein when measured by IHC. Only three specimens showed HER-2/neu gene amplification by FISH. There was no correlation between the results obtained by IHC and FISH. Conclusions: The lack of concordance between IHC and FISH makes it unlikely that overexpression of the HER-2/neu protein in germ cell tumours is of prognostic or therapeutic relevance. Because of the low rate of HER-2/neu gene amplification in germ cell tumours, a clinical trial of trastuzumab treatment in patients with germ cell tumours is not warranted.